THE RELATIONSHIP OF PARTNER SUPPORT WITH VARIOUS ACTIVITIES OF THE ELDERLY HYPERTENSION - Angelina, Farah Dwita; Haryanto, Joni; Ulfiana, Elida (Universitas Airlangga, 2021)
Hypertension is a health problem that many elderly suffer from. Blood pressure in the elderly with hypertension can be controlled in various ways, namely doing physical activity regularly, performing activities related to cognitive function, and controlling stress levels so as not to affect contractions or pulsations of the heart and nervous system that can cause blood pressure to increase. The purpose of this study was to determine the relationship of partner support with physical, mental, and social activities of the elderly with hypertension.This study used a correlational non-experimental design with a cross-sectional approach. The number of samples were 102 respondents in the Morokrembangan area, where the sampling used Nonprobability Sampling method, namely Purposive Sampling. The research instrument used partner support questionnaires, Global Physical Activity Questionnaire (GPAQ), mental health practices, social activities and demographic characteristics. The analysis used Spearman Rho test.The results of this study were there was a relationship between partner support with physical activity (p = 0.000; r = 0.589 ), mental activity (p = 0.000; r = 0.778 ), and social activity (p = 0.000; r = 0.671) with positive and unidirectional correlation.As you get older, daily activities will decrease too. The better the support provided by the partner, the higher the level of daily activities carried out by the elderly. Therefore, elderly couples are expected to provide mutual support in carrying out physical, mental, and social activities.